2018
DOI: 10.21833/ijaas.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Students perceptions of audience response system in classroom feedback: A qualitative study

Abstract: The aim of this study was to explore students' attitudes to formative feedback from classroom questions, peer interactions, and post-lecture sessions. We used a qualitative approach involving focus groups interviews. A complete cohort of second-year nursing students (n = 120) attending a therapeutic communication course as part of a Bachelor of Nursing Program participated in this study. Of them, 49 volunteered to contribute to focus group interviews. NVivo (QSR International, Melbourne, Australia) was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Our findings are consistent with other national studies that were conducted among dentistry and nursing students. 12 , 15 Both studies found the ARS system to be an effective tool to enhance student attention, engagement, and overall attitude. Kaleem et al who did not find any change in students’ academic achievements but stated their belief that the fun environment fostered by the ARS could eventually result in higher student achievement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with other national studies that were conducted among dentistry and nursing students. 12 , 15 Both studies found the ARS system to be an effective tool to enhance student attention, engagement, and overall attitude. Kaleem et al who did not find any change in students’ academic achievements but stated their belief that the fun environment fostered by the ARS could eventually result in higher student achievement.…”
Section: Discussionmentioning
confidence: 99%
“…Ismaile and Alhosban found that the immediate feedback and anonymity available via ARS technology-enhanced nursing students’ peer discussions at Princess Nourah bint Abdulrahman University (PNU) and improved their understanding of a lecture’s main concepts. 12 A study by Almanasef et al at King Khalid University found that using a flipped classroom technique for pharmacy students increases their satisfaction and engagement with their peers and with the instructor more than a traditional class. 3 Studies in Saudi Arabia have only assessed the impact of either flipped classroom techniques or ARSs separately and never integrated the two.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it also helps the respondents to freely present their personal opinions, without social pressure as in the group interview. In the qualitative study, with the same question, individuals perceive and explain differently depending on their personal experience (Ismaile and Alhosban, 2018). Although qualitative research does not answer research questions in specific numbers as quantitative research, it provides detailed answers to research questions about many aspects of the problem.…”
Section: Research Methodsologymentioning
confidence: 99%
“…The motivational learning ambivalence inside the class reflects more the teaching-learning activities the teachers are employing inside that specific part of the international nursing program learning environment. Student nurses have shown that feedback from lecturers and peers influence learning (Ismaile and Alhosban, 2018). The unraveled experience shows that this process is disrupted by language barriers.…”
Section: Theme 2: Communicative Struggle Within the Divergence Of Reamentioning
confidence: 99%